Floodplain restoration on the Upper Danube by re-establishing back water dynamics: first results of the hydrological monitoring - Fischer, Peter; Cyffka, Bernd (ERDKUNDE, 2014)
Reactivation of hydrological dynamics is an essential part within restoration projects especially on floodplains. Frequently, oxbows are reconnected or former flood channels are supplied with water again. This can be accomplished for example by lowering spillway weirs, slit dams or widening of passages. In highly developed areas with various stakeholder interests and different types of land use the floodplain often is connected with the river via controllable sluices. This contribution explains the importance of a controlled water management of sluice gates for the interplay between river and an artificially connected floodplain. First results of the hydrological monitoring can be achieved by the interpretation of hydrographs and ground water levels as well as mapping surveys of flooded areas with a GPS. The functionality and effectiveness of restoration measures implemented in the research area on the Upper Danube between Neuburg and Ingolstadt are assessed and discussed. It is possible to point out that the different types of land use (forestry, nature conservation, water management and hydropower) within a river and its adjacent floodplain can only be brought together by an optimized control of the restoration measures themselves. The possibilities and constraints of an optimum discharge control, the major objective of this research, are discussed.